Chemotherapy-Induced Peripheral Neuropathy - Jain, Ashish; Hariprasad, MG; Sharique, Mohammad; Redhwan, Moqbel Ali Moqbel (Indian Journal of Pharmaceutical Education and Research, 2023)
Chemotherapy-induced peripheral neuropathy is a frequent and dose-limiting complication of chemotherapeutic drugs such as platinum-based compounds, taxanes, vinca alkaloids, bortezomib, and thalidomide that damages peripheral nerves and has a severe influence on patients' well-being and sickness outcomes. Manifestations of CIPN include numbness, tingling, neuropathic pain, cramping, and trouble handling small objects and walking. Recent research in the CIPN pathogenesis has revealed new strategies and pathways for developing novel therapies that can be scrutinized clinically to improve the management of this devastating toxicity. Unfortunately, no single agent is completely protective against this adverse effect, and because no single treatment option works for everyone, duloxetine is the only treatment option that can be recommended. After a thorough review, alternative therapeutic options such as antidepressants, gabapentin, pregabalin, tricyclic and topical gels containing baclofen and ketamine can be considered. In addition, Vitamins, Omega-3 fatty acids, Calcium, Magnesium, Cannabinoids, Melittin, and other natural products, as well as non-drug methods such as exercise, may be used to reduce the adverse effects of CIPN treatment medications. This review focuses on the new strategies for the prophylactic and therapeutic approaches of CIPN, including pharmacological and non-pharmacological methods.
Keywords: Chemotherapy-induced peripheral neuropathy; Mechanism of CIPN; Prophylactic and Therapeutic approaches of CIPN